The Influence of the Physical Home Environment and the Habits of Patients with the Incident of Pulmonary Tuberculosis in the Working Area of the Somambawa Puskesmas, Somambawa District, District South Nias Year 2022 - Susanti br Perangin-angin; Soni Lisa Br Tarigan (International Journal of Educational and Life Sciences, 2024)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis which infects about 10 million people causing the death of 1.3 million people worldwide, making it one of the environmental-based diseases that is still a public health problem. This situation was closely related to environmental factors, clean and healthy living behavior, and also the virus itself. Type of research was an analytic observational study, with a case control design where the population of this study was all pulmonary tuberculosis patients who are recorded in the tuberculosis registration book at the Somambawa community Health Center starting from January 2022 - June 2022 with a sample of 28 cases and 28 controls. Determining the influence of physical environmental factors and habits of patients with the incidence of tuberculosis. The data obtained were grouped based on the characteristics and risk factors for the incidence of tuberculosis which were analyzed univariately and bivariately using the Chi Square test at a 95% confidence level. The results showed that the humidity variable obtained p = 0.001 and OR = 0.10, temperature with p = 0.044 and OR = 0.162, occupancy density p = 0.006 and OR = 0.163, and the behavior of opening and closing windows p = 0.012 and OR = 0.188. It can be concluded that humidity, temperature, population density, and behavior of opening and closing windows have an influence on the incidence of tuberculosis in the working area of ​​the Somambawa community health center, Somambawa sub district, Nias Selatan district in 2022. It is hoped that they can try to be independent in improving healthy houses by being able to be more routine in opening and closing windows, maintaining cleanliness, and being able to try independently in realizing healthy homes so that they can break the chain of spread of pulmonary tuberculosis.